2021
DOI: 10.3892/ol.2021.13015
|View full text |Cite
|
Sign up to set email alerts
|

EGFR and ERK activation resists flavonoid quercetin‑induced anticancer activities in human cervical cancer cells in vitro

Abstract: In the present study, due to the complex and numerous targets of Sarcandrae Herb (also known as Zhong Jie Feng), network pharmacology was performed to analyze its therapeutic effect on 2 cervical cancer cell lines, which could assist with the development of novel therapies. The results suggested that the natural flavonoid quercetin (Que), the effective antitumor ingredient in SH, which is widely present in a variety of plants, may depend on the target, EGFR. Previous studies have shown that EGFR serves a cruci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 51 publications
2
7
0
Order By: Relevance
“… 21 Previous studies have established that p21 can arrest the cell cycle in the G1 phase by interacting with cyclin D/CDK. 22 , 23 In our study, over‐expressed RACK1 led to p21 expression down‐regulation without affecting the expression of p53, indicating that p21 functions in an independent way on p53 in the development of CC with RACK1 dysregulation. However, considering the versatility of RACK1 in different types of human tumors, further research studies to clarify its function are still needed.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“… 21 Previous studies have established that p21 can arrest the cell cycle in the G1 phase by interacting with cyclin D/CDK. 22 , 23 In our study, over‐expressed RACK1 led to p21 expression down‐regulation without affecting the expression of p53, indicating that p21 functions in an independent way on p53 in the development of CC with RACK1 dysregulation. However, considering the versatility of RACK1 in different types of human tumors, further research studies to clarify its function are still needed.…”
Section: Discussionsupporting
confidence: 48%
“…p21 was first identified as a downstream gene of p53, subsequent research showed that p21 functions as an important cell cycle regulator, involved in the process of cell growth, differentiation, aging and death 21 . Previous studies have established that p21 can arrest the cell cycle in the G1 phase by interacting with cyclin D/CDK 22,23 . In our study, over‐expressed RACK1 led to p21 expression down‐regulation without affecting the expression of p53, indicating that p21 functions in an independent way on p53 in the development of CC with RACK1 dysregulation.…”
Section: Discussionsupporting
confidence: 48%
“…A natural flavonoid, widely present in many plants (X. Chen et al 2021) possessing strong antioxidant activity (Ekeanyanwu and Njoku 2014) and osteoarthritis healing effects (Choudhary et al 2014) offering potential benefits for human health (Ekeanyanwu and Njoku 2014) .…”
Section: Resultsmentioning
confidence: 99%
“…After autophosphorylation, EGFR directly binds or acts indirectly on the GRB2 complex to activate the Ras protein. The activated Ras activates the downstream serine/threonine protein kinase, and Raf can phosphorylates ERK-1/2 ( Chen et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%